A calcium-dependent lipid binding protein, OsANN10, is a negative regulator of osmotic stress tolerance in rice. (April 2020) - Gao, Shuxin; Song, Tao; Han, Jianbo; He, Mengli; Zhang, Qian; Zhu, Ying; Zhu, Zhengge
Highlights: OsANN10 is a putative annexin protein. OsANN10 is a calcium-dependent lipid binding protein. OsANN10 is a negative regulator of osmotic stress tolerance. Knocking down OsANN10 suppresses cell membrane damage by ROS under PEG induced osmotic stress. Abstract: Annexin, a multi-gene family in plants, is essential for plant growth and stress responses. Recent studies demonstrated a positive effect of annexin in abiotic stress responses. Interestingly, we found OsANN10, a putative annexin gene in rice, negatively regulated plant responses to osmotic stress. Knocking down OsANN10 significantly decreased the content of H2 O2 by increasing Peroxidase (POD) and Catalase (CAT) activities, further reducing oxidative damage in rice leaves, suggesting a negative regulation of OsANN10 in protecting cell membrane against oxidative damage via scavenging ROS under osmotic stress.